Development of a high energy diode-pumped chirped pulse amplification laser system for driving soft x-ray lasers - Reagan, Brendan A., author; Rocca, Jorge, advisor; Menoni, Carmen, committee member; Marconi, Mario, committee member; Krueger, David, committee member (Colorado State University. Libraries, 2012)
There is significant interest in the development of compact high repetition rate soft x-ray lasers for applications. This dissertation describes the development of a high energy, laser diode pumped, chirped pulse amplification laser system for driving soft x-ray lasers in the 10-20 nm spectral region. The compact laser system combines room temperature and cryogenically-cooled Yb:YAG amplifier to produce 1.5 Joule pulses at up to 50 Hz repetition rate. Pulse compression results in 1 J pulses of 5 ps duration. A room temperature pre-amplifier maintains bandwidth for short pulse operation and a novel cryogenic cooling technique for the power amplifier was developed to enable high average power operation of this laser. This laser was used to drive a soft x-ray laser on the 18.9 nm line of nickel-like molybdenum. This is the first demonstration of a soft x-ray laser driven by an all diode-pumped laser.
Keywords: diode; ultrafast; soft x-ray laser; laser